Targeting autophagy process in center nervous trauma - Wei, Shanshan; Leng, Bing; Yan, Genquan (Frontiers in Neuroscience, 2023)
The central nervous system (CNS) is the primary regulator of physiological activity, and when CNS is compromised, its physical functions are affected. Spinal cord injury (SCI) and traumatic brain injury (TBI) are common trauma in CNS that are difficult to recover from, with a higher global disability and mortality rate. Autophagy is familiar to almost all researchers due to its role in regulating the degradation and recycling of cellular defective or incorrect proteins and toxic components, maintaining body balance and regulating cell health and function. Emerging evidence suggests it has a broad and long-lasting impact on nervous system injury diseases and involves a pathophysiological process involving the alteration of autophagy marker expression. Changes in autophagy level are considered a potential therapeutic strategy and have shown promising results in preclinical studies for neuroprotection following traumatic brain injury. However, the relationship between upward or downward autophagy and functional recovery following SCI or TBI is debatable. This article reviews the regulation and role of autophagy in repairing CNS trauma and the intervention effects of autophagy-targeted therapeutic agents to find more and better treatment options for SCI and TBI patients.